(untitled) (The Pakistan Development Review, 2004)
The significance of foreign direct investment (FDI) flows is well documented in literature for both the developing and developed countries. Over the last decade foreign direct investment have grown at least twice as rapidly as trade Meyer, (2003). As there is shortage of capital in the developing countries, which need capital for their development process, the marginal productivity of capital is higher in these countries. On the other hand investors in the developed world seek high returns for their capital. Hence there is a mutual benefit in the international movement of capital.